Two Twelfth-Century Kite Shields from Szczecin, Poland. (3rd July 2019) - Dowen, Keith; Marek, Lech; Słowiński, Sławomir; Uciechowska-Gawron, Anna; Myśkow, Elżbieta
Abstract : The Polish city of Szczecin, located on the Odra river in north-west Poland, has a complex history which is reflected in its excavated material culture. The most remarkable artefacts among the numerous finds of arms and armour from the city are two late twelfth century kite shields found in the area of the early medieval stronghold. Based on our current state of knowledge, these are the only surviving examples of such shields in the world. Of the two shields recovered from Szczecin, the painted example has been published several times in Polish journals and yet it remains largely unknown to the wider European audience. The unpainted shield, however, was only recently identified and its importance fully appreciated. As such this study aims to update the information on the painted shield based on the latest research, and integrate it and the unpainted shield into the wider European archaeological context.